(3EOGQI GdYedjGJ GdeUQajIs - (3OQjO cGed(B, (3Bd THjHs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ(B,s, 2015)
(3jJfGhd ebOeI aj EOGQI GdYedjGJ GdeUQajI,Gdgjcd GdJfXjej hGdbhGFe GdeGdjI ddHfc,eUGOQ Jehjd GdHfhc GdJLGQjI,EOGQI GdehLhOGJ hGdeWdhHGJ GdeUQajI,EOGQI GdeNGWQ GdeUQajI hGdJYKQ GdeUQaj,EOGQI GdEbQGV aj GdHfhc,EOGQI bSe GdNRjfI,EOGQI GdMSGHGJ GdLGQjI,EOGQI GdhOGFY,GdGYJeGOGJ GdeSJfOjI,GdChQGb GdJLGQjI,EOGQI GdGSJKeGQ aj GdChQGb GdeGdjI,GdcaGdGJ GdeUQajI(B((3NWGHGJ GdVeGf(B)(3,HhGdU GdJMUjd,GdMhGdGJ hGdYedGJ GdGLfHjI,JShjb GdNOeGJ GdeUQajI,GdHfhc GdEdcJQhfjIs
(3HjHdjhZQGajG(B: (3U(B.401-408s
Keywords: (3GdCQOfs; (3GdHfhc(B-(3GdMSGHGJ GdeUQajIs